Utility of Magnetic Resonance Imaging Features for Improving the Diagnosis of Idiopathic Intracranial Hypertension Without Papilledema. Issue 3 (September 2019) - Mallery, Robert M.; Rehmani, Obeidurahman F.; Woo, John H.; Chen, Yin Jie; Reddi, Sudama; Salzman, Karen L.; Pinho, Marco C.; Ledbetter, Luke; Tamhankar, Madhura A.; Shindler, Kenneth S.; Digre, Kathleen B.; Friedman, Deborah I.; et al.
Abstract : Objective: Revised diagnostic criteria for idiopathic intracranial hypertension (IIH) were proposed in part to reduce misdiagnosis of intracranial hypertension without papilledema (WOP) by using 3 or 4 MRI features of intracranial hypertension when a sixth nerve palsy is absent. This study was undertaken to evaluate the sensitivity and specificity of the MRI criteria and to validate their utility for diagnosing IIH in patients with chronic headaches and elevated opening pressure (CH + EOP), but WOP. Methods: Brain MRIs from 80 patients with IIH with papilledema (WP), 33 patients with CH + EOP, and 70 control patients with infrequent episodic migraine were assessed in a masked fashion for MRI features of intracranial hypertension. Results: Reduced pituitary gland height was moderately sensitive for IIH WP (80%) but had low specificity (64%). Increased optic nerve sheath diameter was less sensitive (51%) and only moderately specific (83%). Flattening of the posterior globe was highly specific (97%) but had low sensitivity (57%). Transverse venous sinus stenosis was moderately sensitive for IIH WP (78%) but of undetermined specificity. A combination of any 3 of 4 MRI features was nearly 100% specific, while maintaining a sensitivity of 64%. Of patients with CH + EOP, 30% had 3 or more MRI features, suggesting IIH WOP in those patients. Conclusion: A combination of any 3 of 4 MRI features is highly specific for intracranial hypertension and suggests IIH WOP when present in patients with chronic headache and no papilledema.